BIAYA MODAL DAN BIAYA HUTANG DALAM KEUANGAN ISLAM - Muhayatsyah, Ali (Faculty of Islamic Economics and Business, IAIN Lhokseumawe, 2019)
This study discusses financial policies related to costs of capital and costs of debt (capital structure) in the concept of Islamic finance. For a long time capital structure theory has evolved and is used as a reference for evaluating investment decisions for investors and companies that provide a role for managers in making decisions related to the use of company capital so as to improve company performance and value. The current understanding of the cost of equity only refers to the rate of return that is the investor's right to invest in the company. While the cost of debt is understood as the part that must be received from an investment so that the minimum level of return of creditors is met. The underlying theory is, such as the Leverage model; Miller-Modigliani (MM) model; Capital Asset Pricing Model (CAPM); Arbitrage Price Theory (APT); and Gordon's model which has so far been used in financial theories relating to capital structure problems. The concept of capital structure in Islamic finance gives specific emphasis on the use of capital. The concept of self-regulated capital must be in accordance with Islamic law. This means that any use of capital or debt must have a clear purpose in accordance with Islamic principles with the aim of maximizing the problem so that the creation of falah. In the concept of Islamic capital, it is permissible to take a share of profits on capital, but the amount cannot be determined based on a percentage of capital. The profit is an incentive for capital used in business projects, the calculation of which is done after the business process is completed and other obligations have been fulfilled. Keywords: Costs of Capital, Costs of Debt, Capital Structure, Islamic Finance Abstrak Penelitian ini membahas tentang kebijakan keuangan yang berkaitan dengan biaya modal dan biaya hutang (struktur modal) dalam konsep keuangan Islam. Sejak lama teori struktur modal telah berkembang dan dijadikan sebagai rujukan penilaian keputusan investasi bagi investor maupun perusahaan yang memberikan peran kepada manajer dalam mengambil keputusan terkait penggunaan modal perusahaan sehingga dapat meningkatkan kinerja dan nilai perusahaan. Pemahaman selama ini mengenai biaya ekuitas hanya mengacu pada tingkat pengembalian yang merupakan hak investor atas investasinya di perusahaan. Sedangkan biaya hutang dipahami sebagai bagian yang harus diterima dari suatu investasi agar tingkat hasil minimum para kreditor terpenuhi. Teori yang melandasi tersebut seperti, model Leverage; model Miller-Modigliani (MM); Capital Asset Pricing Model (CAPM); Arbitrage Price Theory (APT); dan model Gordon yang selama ini digunakan pada teori-teori keuangan yang berkaitan dengan masalah struktur modal. Konsep struktur modal dalam keuangan Islam memberikan penekanan secara spesifik dalam penggunaan modal.Konsep modal sendiri diatur harus sesuai dengan hukum Islam. Artinya setiap penggunaan modal atau hutang harus memiliki tujuan yang jelas sesuai dengan prinsip syariah dengan tujuan untuk memaksimumkan maslahah sehingga terciptanya falah. Dalam konsep modal Islam memperbolehkan pengambilan bagian keuntungan atas modal namun besarannya tidak boleh ditetapkan berdasarkan persentase dari modal. Laba tersebut merupakan insentif atas modal yang digunakan dalam proyek bisnis yang perhitungannya dilakukan sesudah proses bisnis selesai dan kewajiban-kewajiban lain telah terpenuhi. Kata kunci: Biaya Modal, Biaya Hutang, Struktur Modal, Keuangan Islam